Living Rivers: Trends and Challenges in Science and Management - Leuven, R.S.E.W.; Leuven, R.S.E.W.; Ragas, A.M.J.; Ragas, A.M.J.; Smits, A.J.M.; Smits, A.J.M.; Velde, G.van der.; Velde, G.van der. (Developments in Hydrobiology, 2006)
All over the world, sustainable river basin management is a leading principle of policy plans and legal instruments for water management (e.g. the European Water Framework Directive). The evidence, however, to underpin the full scope of sustainability is rather scanty. In this book an integrative perspective on trends and challenges in river science and management is demonstrated. The three pillars underneath sustainable water management, ecology, economy and sociology, are elaborated by experts in their fields. A number of papers integrate the current knowledge on the structure, functioning and management of ‘living rivers’. The book includes data and experiences concerning the rivers Allier, Meuse, Rhine, Sava and Tagliamento in Europe and the river Illinois in the USA. Sustainable river basin management asks for un-orthodox rehabilitation programmes and ecosystem based and transboundary management approaches.